Contemporary outcomes in women undergoing percutaneous coronary intervention for acute coronary syndromes - Al-Fiadh, A.; Andrianopoulos, N.; Farouque, O.; Yan, B.; Duffy, S.; Charter, K.; Tongyoo, S.; New, G.; Yip, T.; Brennan, A.; Proimos, G.; Reid, Christopher; et al. (2011)
Background: Uncertainty remains as to whether females benefit as much as males from percutaneous coronary intervention (PCI) in the setting of an acute coronary syndrome (ACS). Methods: We compared 802 women with 2151 men presenting with ACS, undergoing PCI from April 2004 to October 2006 from the Melbourne Interventional Group registry. Clinical characteristics, in-hospital, 30-day and 1-year outcomes were compared. Results: Women were older (69.6 ± 11.6 vs. 62.17 ± 12.3 years, p < 0.001), and had more diabetes (27.1% vs. 19.6%, p < 0.001) and hypertension (70.3% vs. 53.9%, p < 0.001) than men. Women were less likely to present with ST-elevation myocardial infarction (30.5% vs. 37.9%, p < 0.001). Bleeding (3.6% vs. 0.8%, p < 0.001) was higher among women. Thirty-day mortality (4.7 vs. 2.4%, p < 0.001) and MACE (10.1 vs. 6.4%, p < 0.001) were higher in women. Gender was an independent predictor of overall MACE at 30 days (OR 1.45, 95% CI 1.04–2.02, p = 0.03) but not death. At 12 months, there were no significant differences in mortality (6.4% vs. 4.8%, p = 0.09), myocardial infarction (5.5% vs. 5.0%, p = 0.64), target vessel revascularization (7.9% vs. 7.0%, p = 0.42) and MACE (16.3% vs. 14%, p = 0.13) between women and men. Conclusions: There is an early hazard amongst women undergoing PCI for ACS, but not at 12 months. These data suggest that gender should not affect the decision to offer PCI but further gender specific studies are warranted.